Why Stakeholder And Stockholder Theories Are Not Necessarily Contradictory: A Knightian Insight - Velamuri, S. Ramakrishna (Journal of business ethics, 2005)
The normative foundations of the investor centered model of corporate governance, represented in mainstream economics by the nexus-of-contracts view of the firm, have come under attack, mainly by proponents of normative stakeholder theory. We argue that the nexusof- contracts view is static and limited due to its assumption of price-output certainty. We attempt a synthesis of the nexus-of-contracts and the Knightian views, which provides novel insights into the normative adequacy of the investor-centered firm. Implications for scholarship and management practice follow from our discussion.